Two new genera and species of Eriococcidae (Hemiptera: Sternorrhyncha: Coccoidea) with new data on the family in Turkey - Kaydan, M. Bora; Kozár, Ferenc (Zootaxa, 2008)
Two new genera, Borchseniococcus gen. nov. and Kotejacoccus gen. nov., and two new species, B. duzgunesae sp. nov., off an undetermined plant, and K. turcicus sp. nov., off Quercus sp., are described in the family Eriococcidae from Turkey. In addition, new faunistical data on 11 other eriococcid species from Turkey are given. In total, the number of scale insects (Hemiptera: Coccoidea) in Turkey is increased to 272, and the number of species in the family Eriococcidae to 25.